Maternal Fetal Attachment Pada Kehamilan Remaja Berdasarkan Analisis Teori Maternal Role Attainment-Become A Mother - Martina Ekacahyaningtyas; Siti Nurjanah (Yayasan Healing and Healthcare Education, 2026)
Pregnancy is a transition in roles that may lead to a woman's emotional susceptibility. The journey of adjusting to pregnancy presents a challenge for a woman in forming a connection between mother and fetus. Adolescent pregnancy adversely affects the health of both the mother and the fetus since the mother is not fully prepared to handle pregnancy. This will influence the physical, mental, and emotional states. Adolescent women who are pregnant during this stage require support from nurses to ensure a smooth transition. Nurses assist women in learning, building confidence, and fostering Maternal Fetal Attachment. This study aims to examine maternal-fetal attachment during adolescent pregnancy through the lens of the Maternal Role Attainment-Become-A-Mother theory. The approach adopted is informed by the theoretical framework established by Meleis. The findings of this study present a theoretical framework for maternal role attainment that can assist adolescent pregnant women in developing Maternal Fetal Attachment with their fetuses. The inference that can be made is that utilizing maternal role attainment theory can strengthen affectionate connections, boost interaction, and deepen emotional ties between mother and fetus. Enhanced maternal-fetal bonding aids in addressing several obstacles of adolescent pregnancy.